Of People and Protest: Spiritual Resistance in Newar Hymns - Phuyal, Komal Prasad (Literary Studies, 2021)
The spiritual and the political at times merge together in the formation of powerful voice of protest in quest of social harmony. This is also seen in Newari cultural landscape. Newari hymns present that the collective imagination poetically transcends beyond the earthly domain of control of authority and social structures, revolting against the prevalent social order. The paper studies two historical Newari hymns “Shitala Maju” and “Bijaya Laxmi” from the perspective of the cultural resistance. When the hymns that are still sung as integral cultural performance in social life of the Newari settlements are analysed to examine the nature of their spiritual quest, the hymns, in the form of devotional poetry, emerge as a sharp critique of the then power structure. This paper argues that the Newari hymns raise the voice of people against the atrocities of both the state and/or the King in the form of spiritual resistance in its inner core though such poems externally display devotion as their primary ethos.